2003
DOI: 10.1111/j.1547-5069.2003.00283.x
|View full text |Cite
|
Sign up to set email alerts
|

Parental Consent and Adolescent Risk Behavior Research

Abstract: Health researchers must understand the methodological, legal, and ethical issues related to parental consent to produce high-quality, valid research about adolescents and to provide evidence for laws, policies, and regulations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
116
1
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(128 citation statements)
references
References 29 publications
7
116
1
1
Order By: Relevance
“…The sample size and opportunistic nature of sampling is a further limitation that prevents us from making firm inferences about the representativeness of our final sample. Conducting alcohol research with under 16s is challenging for many reasons, including the requirement to gain parental as well as child consent (Tyler & Davies, 2013); this can limit the potential pool of respondents (Tigges, 2003), and may also mean that confidentiality is doubted. Whilst the study has good internal validity, the potential generalizability of the results to other population groups is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…The sample size and opportunistic nature of sampling is a further limitation that prevents us from making firm inferences about the representativeness of our final sample. Conducting alcohol research with under 16s is challenging for many reasons, including the requirement to gain parental as well as child consent (Tyler & Davies, 2013); this can limit the potential pool of respondents (Tigges, 2003), and may also mean that confidentiality is doubted. Whilst the study has good internal validity, the potential generalizability of the results to other population groups is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Comparisons of students with active only to students with other forms of parental consent found the active consent group constituted a biased sample under-representing students who were male 7,8,13 , older 7 , less academically competent 8,14 , from minority groups 6,8,13 , absent more often from school 10,…”
mentioning
confidence: 99%
“…Response rates vary widely according to the form of consent required, the extent and mode of contacts with parents and as well as other factors such as the use of incentives. 2 Participation rates in health-related studies under passive consent conditions are often above 90%, [3][4][5][6] i.e. a minority of parents actively refuse permission for their child to participate.…”
mentioning
confidence: 99%
“…Tiggs's study in the United States (2003) found that, when passive parental consent is sought in school based research on adolescent risk behavior, parental permission is typically obtained for 30 percent to 60 percent of those sampled, compared to 93 percent to 100 percent when passive consent is relied on (Tiggs, 2003). Obtaining verbal consent over the phone, as opposed to written consent, is another approach which is considered ethically compliant and one which is effective in encouraging parents to be more responsive (Sime, 2008).…”
Section: Ethically Compliant Practicementioning
confidence: 99%
“…It may bias the sample towards parents who are easier to access and reach, youth who have a good relationship with their parents and have fewer behavioral problems (Moolchan and Mermelstein, 2002). A study in the United States, which synthesized the literature related to the use of parental consent in school-based research on adolescent risk behavior, found that students who secured the consent of their parents were more likely to be female, white, from intact homes with more educated parents and less likely to smoke (Tiggs, 2003).…”
Section: Challenges Posed By the Parental Consent Requirementmentioning
confidence: 99%